Characterization of Fallow Gray Forest Soils according to Magnetic and Spectrophotometric Measurements - L.A. Fattakhova; A.A. Shinkarev; L.R. Kosareva; L.Z. Ikhsanova (Учёные записки Казанского университета: Серия Естественные науки)
The magnetic properties and color characteristics of layerwise samples from the upper part of fallow gray forest soil profiles are studied. The estimation of a possibility to objectively and reliably diagnose the lower boundary of the old-arable horizon is carried out by determining the chromatic components (hue, saturation) and magnetic susceptibility. It is shown that the spectrophotometric measurements of hue and saturation of the layerwise samples of dark-grey forest soils in the CIELAB coordinates can be insufficient for correct diagnosis of the lower boundary of the old-arable horizon. The possibility to objectively and reliably diagnose the lower boundary of the old-arable horizon in fallow dark-gray forest soils is demonstrated experimentally by determining the magnetic susceptibility of their layerwise samples. The boundary is defined by an inflection point on the profile curves of magnetic susceptibility. It is established that selective removal of the soil organic matter by hydrogen peroxide does not influence the profile differentiation of magnetic susceptibility. Magnetic measurements are useful addition to the spectrophotometric evaluation of the color characteristics of the upper profile part of fallow soils. They provide diagnosis of the features of postagrogenic differentiation of the former arable horizon by the magnetic properties.